Jenis-Jenis Arthropoda Permukaan Tanah di Kebun Karet Desa Senamat Kecamatan Pelepat Kabupaten Muaro Bungo Provinsi Jambi - Nurhadi, Nurhadi; Hawani, Nora Fauziah; Zikra, Zikra (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
Soil surface arthropods are soil arthropods that reside and act on the surface of the soil. One of the terrestrial areas that is a habitat for ground-level arthropods is a rubber plantation in Senamat Village, Pelepat District, Muaro Bungo Regency, Jambi Province. This research aims to determine the types of surface arthropods in the rubber plantation. This research is descriptive research. Soil surface Arthropod sampling was carried out in August 2024 using 30 Pitfall Trap traps installed randomly (Random sampling) and measurements (Temperature, pH and soil water content) were carried out directly in the field. The samples obtained were identified based on the body morphology of the Arthropods. The trapped arthropods were 34 species from 11 orders of 27 families, namely Oniscus asellus, Julus virgatus, Polydesmus serratus, Lycosa sp. Oedothorax apicatus, Oxyopes salticus, Herpyllus ecclesiasticus, Latrodectus sp., Pseudoparonella sp., Oncopodura tiegsi, Acanthurella sp., Entomobrya sp., Blattella germanica, Hemithyrsocera palliata, Alydus eurinus, Cofana spectra, Xylosandrus crassiusculu, Canthidium multipunctatum, Canthidium sp.1, Canthidium sp.2, Calosoma scrutator, Trigonotarsus rugosus, Titanolabis colossea, Myara aperta, Teleogryllus commodus, Gryllus assimilis, Dolichopus pugil, Sepsisoma flavescens, Asphondylia sp.1, Scelio sp., Tetramorium facificum, and Oecophylla smaragdina.